Pengaruh Satra Musik Arab Modern pada Lagu Sayyidi Ar-Rais karya Hama Meshary Hamdana - Zahrotul Mukaromah; Rika Astari; Salma Nuraeni; Febriani Indah Wulandari (Lisanan Arabiya: Jurnal Pendidikan Bahasa Arab, 2021)
The study purposes to provide an explanation of the influence of modern Arabic music literature on Arabic music. From this influence can present a song entitled "Sayyidi Ar-Rais". In this song, the researcher can explain the song’s meaning by using the theory of semantic analysis of meaning and qualitative descriptivemethods. The data sources obtained by the researchers were taken from YouTube, journals, books, and social media. So from this data can facilitate researchers in analyzing. From this analysis, the researcher can conclude that the influence of Arabic literature is very influential for poets, especially in the field of Arabicmusic. So Hama Beshary created the song "Sayyidi Ar-Rais" which contains a message of peace due to the conflict in Palestine using a structural approach.